2022
DOI: 10.1155/2022/3623591
|View full text |Cite
|
Sign up to set email alerts
|

Protective Prognostic Biomarkers Negatively Correlated with Macrophage M2 Infiltration in Low-Grade Glioma

Abstract: Tumor-associated Macrophages (TAMs) play a vital role in the progression of glioma. Macrophage M2 has been confirmed to promote immunosuppression and proliferation of low-grade glioma (LGG). Here, we searched for genes negatively correlated with Macrophages M2 by bioinformatical methods and investigated their protective ability for prognosis. LGG and adjacent normal samples were screened out in TCGA and three GEO datasets. 326 overlapped differentially expressed genes were calculated, and their biological func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The results of numerous epidemiological and bioinformatic studies convincingly show the connection of the STON1 gene (its expression) with BC (on a model of BC-specific cell lines (MCF-7)) [97][98][99] as well as the same with other various oncological diseases: pancreatic duct adenocarcinoma [100], lung cancer [101][102][103], colorectal cancer [104][105][106], papillary renal cell carcinoma [107], colon carcinoma (liver metastases) [108], basal cell skin cancer [109], clear cell kidney carcinoma [96], bladder carcinoma [110,111], and glioma [112], including in the GWAS data (lung cancer [103]). It is important to emphasize that, according to our in silico data (obtained from the regBase-CAN database), the BC-associated locus rs201414717 PPP1R21 considered in this work and the seven SNPs strongly linked to them are the most likely drivers of the occurrence of tumors ("likely cancer driver").…”
Section: Discussionmentioning
confidence: 78%
“…The results of numerous epidemiological and bioinformatic studies convincingly show the connection of the STON1 gene (its expression) with BC (on a model of BC-specific cell lines (MCF-7)) [97][98][99] as well as the same with other various oncological diseases: pancreatic duct adenocarcinoma [100], lung cancer [101][102][103], colorectal cancer [104][105][106], papillary renal cell carcinoma [107], colon carcinoma (liver metastases) [108], basal cell skin cancer [109], clear cell kidney carcinoma [96], bladder carcinoma [110,111], and glioma [112], including in the GWAS data (lung cancer [103]). It is important to emphasize that, according to our in silico data (obtained from the regBase-CAN database), the BC-associated locus rs201414717 PPP1R21 considered in this work and the seven SNPs strongly linked to them are the most likely drivers of the occurrence of tumors ("likely cancer driver").…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, in DLBC the 13-component gene signature show a positive correlation for six cells including neutrophils. In agreement, M2 macrophage has been confirmed to promote immunosuppression and proliferation of LGG; on the other hand, T cells and natural killer (NK) cells can be associated with poorer OS and DSS in LGG, both in nonmitochondrial gene signature (Ye et al, 2021;Zhu et al, 2022). Concerning DLBC prognosis, the tumor-associated neutrophils show a poor prognostic, in the same way, Manfroi and colleagues demonstrated that in DLBC patients with a higher ratio of neutrophils had a worse prognosis, both in non-mitochondrial gene signature (Manfroi et al, 2018;Mu et al, 2018).…”
Section: Discussionmentioning
confidence: 69%
“…LGGs are slow-growing tumors with an ineluctable propensity for malignancy [ 19 ]. The biological characteristics of LGG are notably distinct from those of GBM, and it is regarded as a therapeutic window before the malignant change.…”
Section: Discussionmentioning
confidence: 99%